Comparison of Computer-Mediated Learning and Lecture-Mediated Learning for Teaching Pain Management to Pharmacy Students - Jamero, Dana J. (American Journal of Pharmaceutical Education, 2009)
OBJECTIVES: To assess the effectiveness, efficiency, and student satisfaction with computer-mediated instruction (CMI) versus lecture-mediated instruction (LMI) of pain management to doctor of pharmacy (PharmD) students. METHODS: This study compared the instruction of pain management by CMI versus LMI. An examination was administered and a student survey was conducted to determine effectiveness and student perception of efficiency and satisfaction with these teaching methods. RESULTS: Mean examination scores were not significantly different between the 2 groups, with 62 (91%) of the LMI group and 46 (94%) of the CMI group scoring ≥70% (p = 0.73). Efficiency and student perception of learning significantly increased in the CMI group. CONCLUSIONS: CMI appears to be at least as effective as LMI in teaching pain management to pharmacy students and students perceive that efficiency and learning is increased with CMI. Therefore, CMI seems to be a viable teaching option.